POSSIBLE MECHANISM OF SPHEROIDIZING OF GRAPHITE IN CAST IRONS AND SILICON IN SILUMINS - A. M. Galushko; S. P. Korolev (Литьë и металлургия, 2009)
Analysis of regularities, which have common character, for graphite and silicon is carried out.